Response surface for quantifying the effects of NaCl and pH on lettuce - Mainardi, Pedro Henrique [UNESP]; Bidoia, Ederio Dino [UNESP] (FapUNIFESP (SciELO), 2024)
The objective of this work was to evaluate the response surface methodology (RSM), with a large sample size, to investigate the effects of NaCl and pH on the root elongation of lettuce (Lactuca sativa) in vitro. For this, 20 lettuce seeds were placed in sterile Petri dishes with two filter papers at the bottom and 3.0 mL of the sample being tested. A rotatable 2x2 factorial arrangement was used, with two factors and a two-level matrix, incorporating two center points and ±1.41 α axial points. Each treatment group consisted of 40 replicates, resulting in 400 experimental observations. Increasing NaCl concentration from 0.0065 to 2, 700 g L-1 caused a 19.3% decrease in lettuce root elongation. When pH decreased from 7.0 to 1.5, there was a 68.8% decrease in root elongation, but, when it increased from 7.0 to 12.5, there was a 44.9% decrease. The analysis of combined effects showed that the increase in NaCl concentration reduced the ability of the plant to resist changes in pH. The RSM was effective in evaluating the statistical significance of the NaCl and pH factors, including their second-order effects and interactions, as well as in quantifying their effects on the root elongation of lettuce under the experimental conditions. Therefore, the RSM is a valuable tool for interpreting the results and evaluating the sensitivity of multi-factor research, even when dealing with a large sample size.
Superfície de resposta para quantificação dos efeitos de NaCl e pH em alface
Keywords: arranjo fatorial; avaliação de interações; design rotativo; factorial arrangement; interaction evaluation; multi-factor; multifatorial; quantification of effects; quantificação de efeitos; rotatable design